OPTIMALISASI PRAKTIK MANAJEMEN KEUANGAN MASJID SEBAGAI UPAYA MENINGKATKAN KEMAKMURAN MASJID - Mudhofar, Muhammad; Wibisono, Yusuf; Salim, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
ABSTRACT The community activity center placed mosque is greatly influenced by the skills mosque administrators in making the mosque prosperous. Mosque financial management has a strategic position prosperity mosque. There many mosques whose financial management is unprofessionally. This service activity was out at the Al-Muttaqien Mosque, Kepuharjo, Lumajang. The aim this service is to obtain an objective picture of mosque financial management and technical guidance on professional mosque financial management practices effort to prosperity of the mosque. The service method is technical assistance and guidance with stages of observation, problem identification, communication, partner involvement, practice, solution formulation and evaluation. The results the service have made a positive contribution. Takmir provides full support all stages of service, actively dialogue and being involved in technical guidance. All material understood easily and then copied and adapted for use administration of mosque financial management. In material on empowering prosperity of mosques, emerged to make mosques into Islamic centers. This service has helped mosque takmir who originally carried out financial administration simple and traditional manner, change to financial reporting model in accordance with the Statement of Financial Accounting Standards. Keywords: Management, Finance, Mosque Management References Purwaningrum, S. (2021). Optimalisasi Peran Masjid Sebagai Sarana Ibadah Dan Pendidikan Islam (Studi Kasus Di Masjid Namira Lamongan. Inovatif Volume 7, No. 1 Pebruari 2021 e-ISSN 2598-3172 . Siskawati, A., Ferdawati, & Firman, S. (2016). Bagaimana masjid dan masyarakat saling memakmurkan? Pemaknaan akuntabilitas masjid. Jurnal Akuntansi Multiparadigma, Vol 7 (1); 70-80. Suarni, A., & Andayaningsi, S. (2018). Manajemen Keuangan Masjid Sulawesi Selatan di Era Industri 4.0. Laa Maisyir: Jurnal Ekonomi Islam, 5(2). https:// doi.org/10.24252/lamaisyir.v5i2.7288 Sucipto, H. (2014). Memakmurkan Masjid. Grafaindo:Jakarta. Sunarti, N., Lestari, N. N. Y., Yanti, P. P., Asty, L. G. W., Uzlifah, U., & Mayuni, N. K. L. (2019). Pengelolaan Keuangan Desa Dan Sistem Akuntansi Keuangan Desa Dalam Rangka Meningkatkan Kinerja Pemerintah Desa Pacung. Jurnal Ilmiah Akuntansi Dan Humanika, 8(1), 42–50. https://doi.org/10.23887/jinah. v8i.19860.